Comprehensive approach to cybercrime prevention in Arab countries - Alyona Dmitrievna, Tsyplakova (Law, State and Telecommunications Review, 2025)
[Purpose] Given the cross-border nature and technological specificity of cybercrime, international cooperation in combating it is of particular importance, based primarily on national regulation and a regional approach. [Methodology/approach/design] This study is a descriptive investigation of cybercrime prevention in the Kingdom of Saudi Arabia, the United Arab Emirates, the Kingdom of Bahrain, the Sultanate of Oman, the State of Qatar, and the State of Kuwait (GCC member states) mainly based on genetic, systematic-functional and systematization methods. Strategies and policies as elements of criminal policy are reflected in Figures. Technical guidelines and standards as parts of cybercrime prevention are reflected in Tables. [Findings] Chronologically (in the 2010s), computer emergency response teams (CERTs) were the first to be established, which later became accountable to competent authorities (cybersecurity centers) and developed guidance documents in various areas: strategies and policies, technical guidelines, and standards. An exception is the Sultanate of Oman, where a national strategy was approved by the highest official as early as 2003. Moreover, the coordinating bodies have come a long way and have evolved in terms of both competence and status. The focus of individual states on the development of subjects is evident. At the regional level, CERT and related committees have been established to update existing regulation and create platforms to counter electronic abuse. There are other core initiatives such as electronic ambassadors that contribute to cybercrime prevention.